Effect of Monensin on performance of finishing steers - Tobyne, D.; Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
We used 72 Hereford and Hereford x Angus cross yearling steers to further evaluate 200 mg Monensin (trade name Rumensin) per head daily. Monensin improved gain 6.7% and significantly improved efficiency, 12.3%.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Monensin; Performance; Steers